Impact of the first wave of the COVID-19 pandemic on emergency surgical activities at the National Reference University Hospital of N’Djamena - Kalli, Moussa; Moussa, Ali Mahamat; Oumar, Aboulgassim; Ouchemi, Choua (Acta Biomedica Atenei Parmensis, 2021)
Aim of the work: An evaluation of Covid-19 pandemic impact on emergency surgical activities at the CHU-RN in N'Djamena, Chad.Method: A retrospective study of patients admitted to the surgical emergency room during the first wave of the pandemic (April-June 2020). The data were compared to those of patients admitted during the same period in 2019 (control group). Results: A total of 3248 patients were received: 2366 in 2019 and 882 in 2020. Respective reduction of 50% of admissions and 31% of emergency operations were observed. The average age (30 years) and male predominance remained unchanged. The average admission time went from 72 hours in 2019 to 7 days in 2020. We also noticed that digestive emergencies, such as acute generalized peritonitis (6.6% vs 14.4%, p < 0.1) and strangulated hernias (6.6% vs 15.2% p: 0.07) were more severe in 2020.Conclusion: COVID-19 had reduced admissions and urgent surgical interventions.